Exploring Indonesian Non-English Majors’ Attitudes toward TikTok Soundtracks for L2 Vocabulary Learning - Lemmuela Alvita Kurniawati; Jonathan Rainer Bunnu (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Despite the growing research on TikTok as a language learning tool, studies examining TikTok soundtracks to learn L2 vocabulary are still scarce, especially among non-English major students in Indonesia. This study aims to investigate Indonesian non-English-major university students’ attitudes and perceptions towards the use of English TikTok soundtracks for second language (L2) vocabulary learning. An explanatory sequential mixed-methods design, using a nine-item Likert-scale questionnaire distributed to 117 participants from 54 universities across 17 provinces in Indonesia. Semi-structured interviews were conducted with six purposively selected participants. Quantitative findings revealed positive attitudes across four categories: perceived effectiveness, emotional engagement, convenience, and perceived enjoyment, with a mean score of 3.48. Perceived enjoyment received the highest mean score (M=3.57). Quantitative findings revealed three themes: English TikTok soundtracks help students understand vocabulary in context, provide a supportive, low-anxiety learning environment, and facilitate pronunciation development. Both quantitative and qualitative findings suggest that TikTok functions as an engaging tool for L2 vocabulary learning outside the classroom. The study contributes to the body of research and literature in language education and in the potential of TikTok soundtracks as a complementary resource for vocabulary and pronunciation development in informal learning contexts.